Removal of Suspended Solid, Colour and Ammoniacal-Nitrogen from Leachate Using Aerated Electrochemical Coagulation (AEC) Under The Influence Factors of pH and Electrolysis Duration - Kamarudin, Muhamad Haziq; Mohd Zin, Nur Shaylinda; Mohamad Zailani, Laila Wahida; Mohd Salleh, Siti Nor Aishah; Rashim, Mohamad Fadzly (International Journal of Integrated Engineering, 2023)
The leachate produced by the decomposition of waste in landfills contains toxic substances that pollute the environment and cause health concerns which proper leachate treatment is essential before leachate is directly discharge into the environment. The most important factors to be considered when adopting a leachate treatment are effluent removal performance and the ability of treated effluent to satisfy the standard limit discharge. This study investigates the optimum condition of Aerated Electrochemical Coagulation (AEC), a mix of physical and chemical treatments in removing suspended solid, colour and ammonia from leachate under the influence factors of pH and electrolysis duration. Stabilised leachate from Simpang Renggam Landfill was used as samples for this study. From the data analysis, the highest removal effectiveness was achieved at 10 minutes of electrolysis duration and pH 5 for removal of suspended solid, colour and ammonia with 93%, 93%, and 40%, respectively. Based on the data, integration of the aeration method into electrochemical coagulation in leachate treatment has shown enhancement of the removal efficiency of suspended solid, colour and ammonia. However, only suspended solid satisfy the standard leachate discharge.